Djibouti : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Djibouti. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights Djibouti's expansion of its transportation and utilities infrastructure to leverage its strategic location as a shipping hub and host to military bases. The authorities' development strategy, Vision Djibouti 2035, aims to transform the country into a middle-income economy and a logistics and commercial hub for all of eastern Africa. Growth is estimated to have reached 6.5 percent in 2016, driven by major public sector projects: the railroad to Ethiopia, the construction of several new ports, and a water pipeline from Ethiopia. Inflation rose to 3 percent on average in 2016, reflecting increased food and service prices.